2002
DOI: 10.4049/jimmunol.168.2.793
|View full text |Cite
|
Sign up to set email alerts
|

NK Cell Inhibitory Receptor Ly-49C Residues Involved in MHC Class I Binding

Abstract: Mouse NK cells express Ly-49 receptors specific for classical MHC class I molecules. Several of the Ly-49 receptors have been characterized in terms of function and ligand specificity. However, the only Ly-49 receptor-ligand interaction previously described in detail is that between Ly-49A and H-2Dd, as studied by point mutations in the ligand and the crystal structure of the co-complex of these molecules. It is not known whether other Ly-49 receptors bind MHC class I in a similar manner as Ly-49A. Here we hav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
11
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 60 publications
0
11
0
Order By: Relevance
“…However, determination of the role of I247 in the differential binding to H-2 s cells in that study was incomplete, because the authors did not further define class I MHC molecules that may be involved, nor did they determine whether the reciprocal mutation, T247I, transferred enhanced binding to H-2 s onto Ly-49I. In another study, Ly-49C residues involved in recognition of multiple class I ligands were identified (30). However, no residues were identified in Ly-49C that discriminated between class I MHC alleles, nor was there acquisition of a new class I specificity, such as for H-2D d , upon mutagenesis of this receptor to selected residues from Ly-49A (30).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, determination of the role of I247 in the differential binding to H-2 s cells in that study was incomplete, because the authors did not further define class I MHC molecules that may be involved, nor did they determine whether the reciprocal mutation, T247I, transferred enhanced binding to H-2 s onto Ly-49I. In another study, Ly-49C residues involved in recognition of multiple class I ligands were identified (30). However, no residues were identified in Ly-49C that discriminated between class I MHC alleles, nor was there acquisition of a new class I specificity, such as for H-2D d , upon mutagenesis of this receptor to selected residues from Ly-49A (30).…”
Section: Discussionmentioning
confidence: 99%
“…In another study, Ly-49C residues involved in recognition of multiple class I ligands were identified (30). However, no residues were identified in Ly-49C that discriminated between class I MHC alleles, nor was there acquisition of a new class I specificity, such as for H-2D d , upon mutagenesis of this receptor to selected residues from Ly-49A (30). In contrast, our study has demonstrated that the DcGK sequence in the ␤4 -␤5 loop plays an important role in H-2D k allele recognition.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a model where a single m157 molecule is accessed by either Ly49H, Ly49C(S151G), or Ly49U(S151G), the change of dimerization mode introduced by a variation at position 151 would be crucial to confer or abolish recognition to m157. Mutation studies (40,49) and the three-dimensional crystal structures available for Ly49 proteins (21)(22)(23) have revealed a remarkable variability in the manner by which Ly49 inhibitory receptors bind MHC class I. Much of this variation resides in a degree of plasticity at the dimer interface, which imparts notable changes in subunit orientation.…”
Section: Discussionmentioning
confidence: 99%
“…Site 2 lacks polymorphic cI residues, providing no explanation for the cI selectivity of Ly49s, and leading to site 1 being originally favored as the principal binding site (12,13). However, most (14)(15)(16)(17)(18)(19), but not all (13,20,21), subsequent mutagenic analyses favored site 2 as the physiological binding site for Ly49s. More recently, the structure of a mutant form of Ly49C in complex with K b revealed a third binding mode in which the Ly49 homodimer adopts a more open dimerization state and contains an additional a helical region in the middle of loop 3, allowing interactions with a slightly different site underneath the peptide-binding groove (site 3) via a single monomer unit (3).…”
mentioning
confidence: 99%